Monetary and currency policy management in Asia - Kawai, Masahiro 1947-; Morgan, Peter J. (Economist); Takagi, Shinji 1953- (Edward Elgar, 2012)
"Asian economies strengthened their monetary and currency management after the Asian financial crisis of 1997/1998, and came through the global financial crisis of 20072009 relatively well. Nevertheless, the recent global crisis has presented new challenges."